Respostas
respondido por:
5
Oi, tudo bom?
É só vc pegar a fórmula da função e substituir X pelo valor indicado:
f(x) = 2x+3
f(0) = 2.0+3
f(0) = 0+3
f(0) = 3
f(x) = 2x+3
f(-1) = 2.-1+3
f(-1) = -2 + 3
f(-1) = 1
f(x) = 2x+3
f(2) = 2.2+3
f(2) = 4 + 3
f(2) = 7
É só vc pegar a fórmula da função e substituir X pelo valor indicado:
f(x) = 2x+3
f(0) = 2.0+3
f(0) = 0+3
f(0) = 3
f(x) = 2x+3
f(-1) = 2.-1+3
f(-1) = -2 + 3
f(-1) = 1
f(x) = 2x+3
f(2) = 2.2+3
f(2) = 4 + 3
f(2) = 7
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás